Benchmarking the performance of Malaysia's construction industry - Ismail, Syuhaida (2009)
Malaysia’s construction industry particularly the provision of public infrastructure projects faces various debatable issues of the government’s belt-tightening budget, abandoned public projects, shoddy workmanship, overbudgeted project procurement and unresolved debts in public project provision. The current global economic downturns as well as the fluctuation in the oil prices worldwide have exacerbated the situation. Thus, in materialising the efficiency, accountability for performance, productivity and monetary policy set in confronting those controversial issues, several actions have been undertaken by Malaysian government including strengthening approval procedures, restructuring the implementation process, enhancing viability through risk distribution, reinforcing the institutional and regulatory framework as well as increasing Bumiputera participation in public infrastructure projects. Yet, these endeavours seem not to be the best solution in tackling those problems. Hence, there is a need of benchmarking the performance of Malaysia’s construction industry especially the provision of public infrastructure projects by clearly stipulating the standard regular evaluation and audition through a performance measurement technique known as Key Performance Indicators (KPIs). This paper provides a literature review of the philosophical, conceptual and functions of KPIs in improvising Malaysia’s construction industry performance. The literature will guide the development of KPIs for the assessment of public infrastructure project provision in Malaysia which forms the major part of the research undertaken.